1987
DOI: 10.1159/000111613
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Glycoconjugates Recognized by the HNK-1 Antibody in Mouse and Chick Embryos during Early Neural Development

Abstract: The monoclonal antibody HNK-1 recognizes a carbohydrate epitope present on a host of glycoconjugates which include the glycoproteins neural cell adhesion molecules (N-CAM) myelin-associated glycoprotein and ependymins, and two glycolipids. Other antibodies, including NC-1, L2 and IgM paraproteins from neuropathy patients share similar binding specificity to the same or related sulfated glucuronyl-containing antigen (SGA). To further investigate its possible significance in early development, the distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…We therefore consider the cells in ventral roots of Splotch mutants to be presumptive glial cells, 9 but the discrimination, whether they are peripheral or central glial cells seems difficult. On embryonic day 13.5 they are not well differentiated, and H N K -I antibody does not bind to murine peripheral glia (Holley and Yu 1987). Further studies are needed to solve this question.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore consider the cells in ventral roots of Splotch mutants to be presumptive glial cells, 9 but the discrimination, whether they are peripheral or central glial cells seems difficult. On embryonic day 13.5 they are not well differentiated, and H N K -I antibody does not bind to murine peripheral glia (Holley and Yu 1987). Further studies are needed to solve this question.…”
Section: Discussionmentioning
confidence: 98%
“…A similar situation may occur as for the fucosyltransferase gene family (39), wherein the enzymes differ only slightly in acceptor specificity. Such variations might be responsible for at least some of the marked differences observed in developmental and spatial patterns of HNK-1 immunostaining when different species are compared (7,11).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to human brain tissues, SGGLs have been found in certain murine cerebellar neurons, including Purkinje cells (Chou and Jungalwala, 1988) and neurons in deep cerebellar nuclei (Prasadarao et al, 1990). Expression of SGGLs is developmentally regulated (Schwarting et al, 1987;Holley and Yu, 1987;Jungalwala et al, 1992). Recent studies revealed that SGGLs are also present in brain endothelial cells from rat and bovine brains, and may play an important role in inflammatory responses in the CNS and PNS Kanda et al, 1994Kanda et al, , 1995.…”
Section: Paraglobosidementioning
confidence: 99%